2009
DOI: 10.1021/jp811183a
|View full text |Cite
|
Sign up to set email alerts
|

Formation of an Intramolecular G-Quadruplex of Human Telomere Induced by Poly(l-lysine) under Salt-Deficient Conditions

Abstract: A single-stranded G-tract human telomere DNA sequence is able to fold into intramolecular G-quadruplex structures which may be important for a number of biological processes and disease-related mechanisms. Poly(L-lysine) (PLL) polymer is linear polypeptides with lysine as the repeat unit and has been employed as a gene carrier in achieving targeted delivery of DNA to cancer cells. To explore the influence of PLL on the conformation of Hum24 DNA, we have investigated the interaction of PLL with Hum24 by biophys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…In addition, the band gap energy ( Eg ) of the photocatalyst can be calculated by kubelka‐munk function and the results are expressed in Figure b. It can be calculated that the Eg of Bi 2 MoO 6 is 2.56 eV which is close to the previous research . And the Eg of 5 wt%‐A/B‐V4 composite is 2.39 eV, which is less than pure Bi 2 MoO 6 , increasing the response range to light.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the band gap energy ( Eg ) of the photocatalyst can be calculated by kubelka‐munk function and the results are expressed in Figure b. It can be calculated that the Eg of Bi 2 MoO 6 is 2.56 eV which is close to the previous research . And the Eg of 5 wt%‐A/B‐V4 composite is 2.39 eV, which is less than pure Bi 2 MoO 6 , increasing the response range to light.…”
Section: Resultsmentioning
confidence: 99%
“…It can be calculated that the Eg of Bi 2 MoO 6 is 2.56 eV which is close to the previous research. [49] And the Eg of 5 wt %-A/B-V4 composite is 2.39 eV, which is less than pure Bi 2 MoO 6 , increasing the response range to light.…”
Section: Optical Absorption Propertiesmentioning
confidence: 91%
“…The slight blue shift in the emission band from 520 nm to 515 nm, similar to that of the phosphors obtained from solid-state reaction, may be attributed to the changes in the crystal field around Eu 2+ arising from the nanosized particles. Zhang et al [12] reported that the particles with nanometer size make the surface energy increase, which causes variation of the crystal field around the local environment of Eu 2+ . Since the excited 4f 6 5d 1 configuration of Eu 2+ ion is greatly sensitive to the lattice environment and 5d electrons can be strongly coupled with the lattice, the mixed states of 4f and 5d are split by the crystal field, which may lead to the shift of the emission peak toward shorter wavelength.…”
Section: Methodsmentioning
confidence: 99%
“…Apart from the ubiquitous potassium or sodium cations, positively-charged polyamines and triethylene tetraamine may contribute to the G4 stability and induce biologically-relevant effects [25,26]. In this context, also the polycationic PLL was evaluated for its impact on the formation of G4 structures by the human telomere in cation-deficient media and showed the interesting ability to convert the telomeric G4 from the antiparallel to the parallel topology [27]. However, to our knowledge, no study has yet been published on the interaction of α,ε-PLL with any G4 DNA.…”
Section: Introductionmentioning
confidence: 99%